2022
DOI: 10.1017/s0143814x21000222
|View full text |Cite
|
Sign up to set email alerts
|

Fifty shades of deservingness: an analysis of state-level variation and effect of social constructions on policy outcomes

Abstract: A patchwork of policies exists across the United States. While citizens’ policy preferences in domains such as the criminal legal system, gun regulations/rights, immigration, and welfare are informed by their political predispositions, they are also shaped by the extent to which policy targets are viewed as deserving. This article centres the idea that collective evaluations matter in policymaking, and it ascertains whether subnational levels of deservingness evaluations of several target groups differ across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…The second explanation policymakers offered for the balance-wheel phenomenon is that higher education institutions have access to other sources of revenue, unlike other areas in the state budget. In alignment with our theory and prior work on the factors associated with perceptions of deservingness ( Kreitzer et al, 2022 ; Oorschot, 2000 ), policymakers viewed higher education institutions as less deserving of state support than other sectors because they had lower levels of need, given their access to nonstate funding streams. In Texas, a legislator explained, “there is an assumption .…”
Section: Thematic Findingssupporting
confidence: 71%
“…The second explanation policymakers offered for the balance-wheel phenomenon is that higher education institutions have access to other sources of revenue, unlike other areas in the state budget. In alignment with our theory and prior work on the factors associated with perceptions of deservingness ( Kreitzer et al, 2022 ; Oorschot, 2000 ), policymakers viewed higher education institutions as less deserving of state support than other sectors because they had lower levels of need, given their access to nonstate funding streams. In Texas, a legislator explained, “there is an assumption .…”
Section: Thematic Findingssupporting
confidence: 71%
“…Reich and Barth (2017) find that the NRA has been successful in relaxing state‐level gun laws through lobbying during the Obama administration in states that were more conservative. This was further supported by Kreitzer and others (2022) who found that a state's perception of the NRA is correlated with how strict their gun policies are. The more conservative a state is, and the fewer minorities it has, the looser its gun control laws are.…”
Section: Resultsmentioning
confidence: 56%
“…Three factors seem especially relevant in understanding how policy attributes might shape voter behavior in the case of student debt relief: evaluations of beneficiary deservingness, preferences for universal versus targeted policy design, and self-interest. Scholars have demonstrated a clear link between how people evaluate the deservingness of beneficiaries and their support for social policies (Kreitzer et al, 2022; Schneider and Ingram, 1993). In general, beneficiaries are viewed as more worthy of government assistance when they demonstrate need, are perceived as hardworking, and are perceived as not responsible for their misfortune (Van Oorschot 2000).…”
Section: Study 1: Policy Details and Political Mobilization For Debt ...mentioning
confidence: 99%